Incidence of COVID-19 in children and young people who play federated football - Seijo Bestilleiro, R.; Suanzes Hernández, J.; Batalla Bautista, D.; Pereira Rodríguez, M. J.; González Martín, C.; Garcia Rodriguez, M. T.; Pértega Díaz, S. (Sports Health: A Multidisciplinary Approach, 2022)
Aim: To determine the incidence of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) infection in children and young people who play federated football. Methods: Prospective study, from October 2020 to January 2021, in players aged 4 to 19 years from federated football clubs in Galicia, Spain (N = 23,845). Outbreaks and cases of SARS-CoV-2 infection were recorded. The cumulative incidence was compared with the incidence registered in Galicia in the same age range. Results: The cumulative incidence was 29.8 cases per 10,000 licenses in 4 months, lower than the incidence registered in the general population for all ages and both sexes (283.7 per 10,000 inhabitants; rate ratio = 9.5). It was higher in January (40.7 per 10,000), coinciding with the population peak. More cases were registered in futsal (42.9 vs 27.5 per 10,000) and competitions with periodic screenings (127.4 vs 9.1 per 10,000). There were 2 outbreaks in 2389 teams (0.08%). Conclusion: The results support the safety of football practice in children and young people with prevention protocols.